Aktualisasi Makna Jihad dalam Kehidupan Modern - Saoki, Saoki (Prodi Siyasah (Hukum Tata Negara) Fakultas Syari'ah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article discusses about the essence of the meaning of jihad and its actualization in a modern life. Basically, jihad has two meanings; First, the notion of the propagation of Islam in a polite, tolerant, peaceful way, and away from coercion and violence. Second, the notion of war. Jihad in the first sense to be applied anytime and anywhere, while the second one should only be applied in a very constrained condition because of the definite threat of the enemy. The main purpose of jihad is al-amr bi al-ma'ruf wa al-nahy an al-munkar. Therefore, in today?s modern context, jihad could be interpreted in a more macro and holistic sense, so that any forms of al-amr bi al-ma'ruf wa al-nahy an al-munkar like an attempt to increase the level of education of Muslims, an attempt to increase the welfare of the Muslims weather economically, politically, and culturally. All are included in a category of jihad in Islam, and they are more important than a physical jihad with a war, due to the current context, jihad with those meanings are the most needed by Muslims.Keywords: Actualization, Jihad, modern age